Peningkatan Hasil Belajar PAK dengan Metode PBL Berbantuan Metode Reward Kelas V SDN 101791 Deli Serdang - Heri Septian Berutu; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research is motivated by the problem, namely the low learning outcomes of students in Catholic Religion subjects regarding the subject of women and men being called to develop. The low learning outcomes of students are caused by various factors, including teachers still using domination methods in the learning process, causing the learning process to become passive and boring, also causes low student learning outcomes. In connection with the problems above, through the Problem Based Learning method, it is hoped that the right way to improve the quality of Catholic Religion learning at SDN 101791 Deli Serdang is to improve student learning outcomes with the help of Reward media. It is hoped that it can improve student learning outcomes regarding the material Women and Men are Called to Develop. The method used in this research is classroom action research (PTK), using the classroom action research model from Kemmis & McTaggart which consists of four stages, namely: planning, implementation, observation and reflection. These four stages were carried out in two research cycles where each cycle focused on material about Women and Men Called to Develop using the PBL method. This research was carried out at SDN 101791 Deli Serdang with research subjects being class V students. The aim of this research is to find out whether the use of the Problem Based Learning model assisted by Reward media can increase the creativity of Phase C students in class V on the material Women and Men Are Called to Develop. And to find out how the use of the Problem Based Learning model assisted by Reward media can improve student learning outcomes. The results of the research in Chapter IV which has been presented in two cycles, and which have been analyzed, can be concluded that the Problem Based Learning model can increase the creativity of Phase C students with the help of Reward Material: Women and Men Are Called to Develop, with an average student score of 77.75 in cycle 1 and cycle 2 there was an increase in the student average to 90.37, thus the student's independent learning results increased by 25% from the observation results of Cycle 1 and cycle 2, so reward media can improve student learning outcomes. The material for women and men is called to develop.